Placental Vascular Malperfusion in Pregnancies With Congenital Heart Disease - Nour Rahnama, MD; Arthur Colson, MD, PhD; Pamela Baldin, MD, PhD; Agnès Pasquet, MD, PhD; Damien Gruson, MD, PhD; David Vancraeynest, MD, PhD; Christophe Beauloye, MD, PhD; Frédéric Debiève, MD, PhD; Sophie Pierard, MD, PhD (JACC: Advances)
Background: Advances in congenital heart disease (CHD) management have improved survival rates, resulting in a growing population of women of childbearing age with CHD. These women face higher risk of obstetric and neonatal complications during pregnancy. While the underlying mechanisms remain unclear, previous studies have identified maternal vascular malperfusion (MVM) in their placentas. Objectives: This study aimed to compare the prevalence of MVM in pregnant women with CHD to those without CHD, assess its association with obstetric and neonatal outcomes, and explore potential risk factors for MVM. Methods: In this prospective single-center study, we enrolled pregnant women with CHD who were followed from March 2021 to June 2023, along with a control group matched for age, parity, and body mass index. Placentas were analyzed for MVM using a scoring system based on the Amsterdam Placental Workshop Group Consensus guidelines. N-terminal pro b-type natriuretic peptide assays in the second trimester and echocardiography in the third trimester were performed to evaluate maternal cardiovascular health. Results: Placentas from 39 CHD and 67 control women were analyzed. MVM prevalence was significantly higher in the CHD group compared to controls (56.4% vs 13.4%, P < 0.001). CHD pregnancies had a higher incidence of adverse obstetric and neonatal outcomes, which were independently associated with MVM (RR: 7.2, P = 0.002). No clinical or paraclinical factors were associated with MVM in CHD women. Conclusions: Women with CHD had a higher prevalence of MVM compared to controls, which was associated with adverse pregnancy outcomes. However, no clinical or paraclinical risk factors for MVM were identified.